1994
DOI: 10.1073/pnas.91.2.669
|View full text |Cite
|
Sign up to set email alerts
|

Waves and stimulus-modulated dynamics in an oscillating olfactory network.

Abstract: The temporal dynamics of electrical activity in an olfactory organ, the procerebral lobe of the terrestrial mollusc Limax maximus, is studied. The lobe exhibits intrinsic oscillations in its field potential. Intracellular recordings show that the lobe contains two classes of neurons, both with activity phase-locked to the oscillation. Neurons in one class produce periodic bursts of spikes while those in the other class rre infrequently but receive strong, periodic inhibition whose onset coincides with the burs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
101
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(103 citation statements)
references
References 19 publications
2
101
0
Order By: Relevance
“…Spatial hypotheses include (1) odor encoding by the locations of a few highly activated and specific glomeruli (Sharp et al, 1975;Mori et al, 1992), (2) the spatial pattern of a large number of glomeruli activated by the odor (C inelli et al, 1995), or (3) both of the above (C inelli et al, 1995;Friedrich and Korsching, 1998;Rubin and Katz, 1999). On the other hand, in additional to the spatial patterns, the temporal sequences in which the cells/glomeruli were activated could also carry information about the odor (Delaney et al, 1994;Gervais et al, 1996;Laurent et al, 1996;Stopfer et al, 1997). Insect neurons fired in an odor-specific succession of assemblies synchronized with local field potential oscillations Stopfer et al, 1997).…”
Section: Temporal Encoding Of Odorsmentioning
confidence: 99%
“…Spatial hypotheses include (1) odor encoding by the locations of a few highly activated and specific glomeruli (Sharp et al, 1975;Mori et al, 1992), (2) the spatial pattern of a large number of glomeruli activated by the odor (C inelli et al, 1995), or (3) both of the above (C inelli et al, 1995;Friedrich and Korsching, 1998;Rubin and Katz, 1999). On the other hand, in additional to the spatial patterns, the temporal sequences in which the cells/glomeruli were activated could also carry information about the odor (Delaney et al, 1994;Gervais et al, 1996;Laurent et al, 1996;Stopfer et al, 1997). Insect neurons fired in an odor-specific succession of assemblies synchronized with local field potential oscillations Stopfer et al, 1997).…”
Section: Temporal Encoding Of Odorsmentioning
confidence: 99%
“…In terrestrial gastropods, the importance of the procerebrum for olfactory information processing was shown (Delaney et al 1994;Gelperin 1999;Gelperin and Tank, 1990), and the neuroanatomy and function of the cerebrum with respect to olfactory information processing was reviewed by Chase (2000). However, only little is known about the olfactory pathway from the sensory cells to higher centres.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that processes of several olfactory receptor neurons establish synaptic contacts at the level of the tentacle ganglion (TG), which is the first relay site; meanwhile other contacts directly reach the PC or project outside the PC (Chase and Tolloczko 1993;Ratté and Chase 2000). PC neurons display a resting cyclic electrical activity of 0.7 Hz, which is important for the storage of odor memory and odor discrimination (Balaban and Maksimova 1993;Delaney et al 1994;Gelperin and Tank 1990;Schütt et al 2000). This oscillatory activity was shown to be modulated by odor stimuli Gelperin and Tank 1990;Gervais et al 1996;Kimura et al 1998;Kleinfeld et al 1994) and by signal molecules such as nitrogen and carbon monoxide, c-aminobutyric acid, 5-hydroxytryptamine (5-HT), dopamine (DA), glutamate (Glu), acetylcholine (ACh) and endogenous neuropeptides such as FMRFa and catch-relaxing peptide, which are present in the PC Cooke and Gelperin 1988;Elekes and Nassel 1990;Gelperin et al 1993Gelperin et al , 2000Hernadi et al 1995;Inoue et al 2001;Kobayashi et al 2010).…”
Section: Introductionmentioning
confidence: 99%